PENGARUH PROFITABILITAS, CASH POSITION DAN KEPUTUSAN INVESTASI TERHADAP KEBIJAKAN DIVIDEN DENGAN KEBIJAKAN UTANG SEBAGAI VARIABEL MODERATING - Arthur Simanjuntak (Jurnal Ilmiah METHONOMI, 2015)
The objective of the research was to examine the influence of Profitability Cash Position and Investment Decision on Dividend Policy with Debt Policy as moderating variables in manufacture companies listed in BEI (Indonesia Stock Market) in the period of 2010 – 2013. The research used causal research method. The population was 136 manufacture companies listed in BEI in the period of 2010-2013, and 35 of them were used as the samples, taken by using purposive sampling technique. The data were analyzed by using residual test. The result of this study showed that simultaneously the variables of Profitability (RAO), Cash Position (CP) and Investment Decision (PER) had influence on Dividend Policy. Partially, Profitability (ROA), and Cash Position (CP) had significant positive influence on Dividend Policy (DPR). The variables of Debt Policy (DER) is moderating variables to explain influence Profitability (ROA), Cash Position (CP) and Invsetment Decision (PER) on Dividend Policy.